Redescription of Suctarsonemus litteratus (Mahunka, 1973) (Prostigmata: Tarsonemidae) - Rezende, José M. [UNESP] (2017)
A redescription of Suctarsonemus litteratus (Mahunka) with new line drawings, micrographs, and measurements is provided. In addition, a key to separate the species of the genus Suctarsonemus is presented.